1995
DOI: 10.1016/0370-2693(94)01564-s
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of the pion pole in p → n charge-exchange scattering

Abstract: A recent experiment at LEAR, the CERN Low Energy Antiproton Ring, has provided very precise dierential cross-section data for the pp ! nn chargeexchange reaction. When performing the extrapolation procedure to the pion pole originally proposed by G. F. Chew the data exhibit the same dynamical mechanism than the np ! pn line reversal reaction. The residue at the pole is consistent with the known value of the charged NN coupling constant, as expected from charge conjugation invariance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…In Refs. [323,324] is was shown that g NN could be extracted with good precision from the data of a single experiment, in a model independent way by extrapolating the data to the pion pole. Like in the NN case, a "low" value for g 2 NN was obtained, which has been a matter of concern and discussion [325].…”
Section: Pp Charge-exchange Dierential Cross-sectionmentioning
confidence: 99%
“…In Refs. [323,324] is was shown that g NN could be extracted with good precision from the data of a single experiment, in a model independent way by extrapolating the data to the pion pole. Like in the NN case, a "low" value for g 2 NN was obtained, which has been a matter of concern and discussion [325].…”
Section: Pp Charge-exchange Dierential Cross-sectionmentioning
confidence: 99%
“…In the above expression E cm is the center of mass energy. In fact, these new data give a very precise value for g 2 πN N /4π [1,4,5], a value which is smaller than the accepted value by about 5%. Recently the Nijmegen group, who analyzed both the N N data [6] and the N N data [7] within a OBEP model, also advocated a smaller value for g 2 πN N /4π.…”
Section: The Strength Of the Pion Nucleon Couplingmentioning
confidence: 62%
“…We select events (from the one prong and the minimum bias data) with exactly one or exactly three long tracks with a total charge of -1 and with at most four photons. The missing mass square was calculated MM 2 = ( E pd ; X E i ) 2 ; ( X p i ) 2 (1) with the sum extending over all seen charged and neutral particles, and it was required that the missing particle had a mass consistent with that of a proton: jMM 2 ; m 2 p j < 0:5 GeV 2 (2) Monte Carlo simulation showed that this cut does not lead to signi cant losses in the number of good events. But the cuts are su cient to identify the signals and to keep the background at an acceptable level.…”
Section: Data and Data Reductionmentioning
confidence: 99%